Reports of Judgments, Advisory Opinions and Orders: Application of the International Convention for the Suppression of the Financing of Terrorism and of the International Convention on the Elimination of all Forms of Racial Discrimination (Ukraine v. Russian Federation) - International Court of Justice (United Nations, 2022)
Preliminary objections